2019
DOI: 10.3390/bs9070078
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Adolescents with Severe Asthma and in Their Parents: Preliminary Results after 1 Year of Treatment

Abstract: Emotional problems, such as anxiety and depression, are a relevant co-morbidity in severe asthma. Anxiety and depression may also be common in the parents of asthmatic adolescents. The current study evaluated anxious and depressive symptoms in 40 adolescents suffering from severe asthma, and in their parents, before and after 1 year of treatment, tailored according to validated asthma guidelines. We used the HADS (Hospital Anxiety Depression Scale) questionnaire for the adolescents, and HADS, STAY (State-Trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…HADS-A and HADS-D scores observed for MF in this study are in the range of scores reported for severe psoriasis (29) and are partly higher than in patients with malignant melanoma stage Ia (50). In comparison with non-dermatologic diseases, the HADS results of this study are in the range of values observed in adolescents with severe asthma, coronary arteria disease, or dialysis (51)(52)(53). Strikingly, PUVA led to a significant decrease in overall HADS-A and HADS-D (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…HADS-A and HADS-D scores observed for MF in this study are in the range of scores reported for severe psoriasis (29) and are partly higher than in patients with malignant melanoma stage Ia (50). In comparison with non-dermatologic diseases, the HADS results of this study are in the range of values observed in adolescents with severe asthma, coronary arteria disease, or dialysis (51)(52)(53). Strikingly, PUVA led to a significant decrease in overall HADS-A and HADS-D (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“… 1 , 2 The global health burden of severe allergic diseases is relevant since patients may experience disability, anxiety and emotional distress, social restrictions, and reduced quality of life (QoL). 3–6 Despite some progress made in understanding the pathogenesis of atopic diseases, significant differences in clinical characteristics, treatment response, and natural history have been described in many allergic patients treated with conventional therapies. To date, studies that aim to identify potential cellular and molecular signature (endotypes) have given rise to new targeted and specific treatment strategies for precision medicine and individualized therapies in allergic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Some psychological approaches have suggested that children could have psychological adjustment difficulties because of an allergy and its symptoms, 25 or that these could be influenced by intra-familial or socio-emotional factors related to family circumstances. [26][27][28][29] Others have explored the relationship with an underlying biological process related to the serotoninergic system. 30,31 In spite of these evidences, there is a lack of studies assessing outcomes with well-validated instruments that compare a clinical allergic sample with a similar control sample of non-allergic children.…”
Section: Introductionmentioning
confidence: 99%